3 willows : the sisterhood grows - Brashares, Ann. (New York : Delacorte Press, 2009)
Ama, Jo, and Polly, three close friends from Bethesda, Maryland, spend the summer before ninth grade learning about themselves, their families, and the changing nature of their friendship.
Keywords: Best friends -- Fiction; Friendship -- Fiction; Interpersonal relations -- Fiction; Conduct of life -- Fiction; Bethesda (Md.) -- Fiction